The Role of Digitalization as a Moderator of the Relationship Between Intellectual Capital and Public Service Quality at the Village Level - Hamdani, Deky; Efrianto, Efrianto; Anugrah, Fadli; Hendra, Hendra (The Future of Education Journal, 2026)
This study aims to analyze the role of digitalization as a moderating variable in the relationship between intellectual capital and public service quality at the village level. The background of this research is based on the need for villages to improve the effectiveness of public services amid technological developments and growing public demands for fast, transparent, and accountable services. The study employed a quantitative approach using SEM PLS to examine both direct and moderating effects, involving 100 respondents consisting of village officials and service users. The findings reveal that intellectual capital significantly influences public service quality, and digitalization also contributes directly to enhancing service effectiveness. Furthermore, digitalization is proven to moderate the relationship between intellectual capital and service quality, indicating that the use of technology strengthens the contribution of human competencies in delivering higher quality services. The discussion highlights that the integration of intellectual capital and digitalization is essential for achieving modern and responsive village-level public services. This study concludes that improving the capabilities of village apparatus and increasing the adoption of digital technologies should be carried out simultaneously to support the transformation of village public services toward a more effective and community-oriented system.